Colorectal Microcarcinoids in Association with Long-Term Exposure to Urinary Content: A Case Report and Review of the Literature - Grace W. Weyant; Dipti M. Karamchandani; Negar Rassaei (Hindawi Limited, 2015)
Long-term exposure of colonic mucosa to urinary content and its association with increased risk of infection, mechanical and biochemical irritation, and malignancy have been described in the literature. Existing case reports and studies depict the low but distinct risk of malignancy in gastrointestinal segments which come in contact with urinary content as a result of surgical correction of urinary tract abnormalities. However, these reports are largely limited to colonic adenocarcinoma and urothelial cell carcinoma. Late urointestinal carcinoma in patients with ileal incorporation into the urinary tract has also been reported. To the best of our knowledge, however, there is only one case report documenting neuroendocrine (NE) cell hyperplasia in colonic mucosa after long-term cystoplasty. Our case is the first to describe microcarcinoids and diffuse NE hyperplasia occurring in a patient with congenital anorectal anomalies, resulting in long-term exposure of colonic mucosa to fecal stream and urinary content. This case, in conjunction with the reported cases in the literature, raises the distinct possibility of an association between exposure of colonic mucosa to urine and long-term development of malignancy, including NE neoplasms.